2010
DOI: 10.1038/jid.2010.5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Human Skin Pigmentation in situ by Repetitive UV Exposure: Molecular Characterization of Responses to UVA and/or UVB

Abstract: Ultraviolet (UV) radiation is a major environmental factor that affects pigmentation in human skin and can eventually result in various types of UV-induced skin cancers. The effects of various wavelengths of UV on melanocytes and other types of skin cells in culture have been studied but little is known about gene expression patterns in situ following in situe exposure of human skin to different types of UV (UVA and/or UVB). Paracrine factors expressed by keratinocytes and/or fibroblasts that affect skin pigme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
110
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 49 publications
4
110
0
Order By: Relevance
“…*p < 0.008 versus control to modulate a large number of genes involved in the pigmentation pathway. In contrast, UVA was not capable of inducing pigmentation-related genes [31]. In our previous observation, we found that after laser toning, UVA-induced melanosis was rather responsive to increasing numbers of laser passes in human (according to Western blotting results).…”
Section: Discussionmentioning
confidence: 87%
“…*p < 0.008 versus control to modulate a large number of genes involved in the pigmentation pathway. In contrast, UVA was not capable of inducing pigmentation-related genes [31]. In our previous observation, we found that after laser toning, UVA-induced melanosis was rather responsive to increasing numbers of laser passes in human (according to Western blotting results).…”
Section: Discussionmentioning
confidence: 87%
“…We found that 4 repetitive low-dose UVA irradiations alone caused an increasing stimulation of the skin's capacity to cope with oxidative stress by +36% compared to the baseline level. Therefore, the beneficial effect of moderate sunlight exposure of the skin is obviously not limited to vitamin D formation [18] , pigmentation [19] or increased expression of antimicrobial peptides [20] .…”
Section: Discussionmentioning
confidence: 99%
“…UVA exposure leads to several lesions, overproduction of ROS (Reactive Oxygen Species) [11], lipid peroxidation (LPO) [4,12] oxidized basis (8-oxo-dG or thymine-glycole), abasic sites and single strand breaks (SSB) [10,12,13]. UVB, absorbed by the epidermis, cause sunburn, erythema and tanning [8] because it is able to induce expression of genes involved in melanin synthesis [14]. UVB is directly absorbed by the proteins and the nucleic acids and leads to the cyclobutane-pyrimidine dimers (CPDs) and pyrimidine pyrimidone photoproducts as the principal DNA lesions [13].…”
Section: Introductionmentioning
confidence: 99%